Multidimensional Deprivation: A Reflection of Urban Concentration in Manipur, India (Economic Journal of Nepal, 2022)
Deprivation is a measure of relative disadvantage socially, economically, and politically that represent a clear picture of the ineffectiveness of various developmental policies leading to resource polarization in a particular sub-group of the population. It means the exclusion of a particular section of society or individuals from certain welfare enhancing facilities. In this paper, multidimensional deprivation in a North-Eastern state, Manipur and its change over time has been examined by using the most recent approach to find out its functional relation with relevant factors. The analysis is done by using different rounds of the two data sets namely, the National Sample Survey and the National Family Health Survey in India. Deprivation measures are decomposed both inter-regionally and across socio-economic groups. The findings of the study do not show any significant relation of deprivation with inequality and poverty. Unlike the traditional expectation of higher remote/rural concentration of deprived people, the poisson regression result points to a higher urban concentration of deprived people. Female-headed households are found to be more deprived. Regionally, the Imphal-West district overtook the Tamenglong District in 2015-16 and became the most deprived district in Manipur. Scheduled tribes (STs) are the most deprived social category in 2011-12 and other backward community (OBC) overtook them in 2015-16. The factors like district (spatial variation), sector, education of the head of household, and Monthly Per Capita Consumer Expenditure have significant impact on deprivation level in Manipur.